Amara (Amara) aeneola Poppius 1906 - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Amara ( Amara ) aeneola Poppius, 1906 Material. Khabarovsk, 19.05.1972, A. Ryabukhin leg., 1♀. Distribution. A boreal East Palearctic species: from Altai in the west to Magadan Region and the mouth of the Amur River in the east, from the tundra zone in the north to South Altai, the Khangai Range, the Greater Khingan, the and southern Sikhote-Alin in the south; south in the mountains. Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 584, DOI:10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734